Éclosions in Literacy Research: Rereading Brandt and Clinton's "Limits of the Local". (June 2022) - Ferguson, Daniel E.; Lemieux, Amélie
In processing the impact of the pandemic amidst other global crises, we found rereading Brandt and Clinton's "The Limits of the Local" article, published 20 years ago next year, to offer much, both theoretically and practically. Written within its own tumultuous time, according to its editors, it argues for transcontextualizing accounts of literacy and employing thingness as a means to subvert local/global dichotomies in literacy studies. In this essay, we reflect on this work 20 years later, and propose an extension of Brandt and Clinton's transcontextualizing perspective through an affirmative ontology of éclosion . We hope this actualization will provide an orientation for furthering transcontextual literacy studies that meet the urgency of our own tumultuous times.